2002
DOI: 10.1046/j.1365-2656.2002.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sociality on short‐distance, female‐biased dispersal in tropical wrens

Abstract: Summary 1.Dispersal from the natal area, or between breeding sites, marks a critical transition for individual animals, and a fundamental demographic and genetic process. Limitations on dispersal in natural populations are important in predicting population dynamics and structure. Tropical habitats that can be naturally patchy are also being fragmented rapidly, and these habitats harbour many social species. 2. We studied dispersal in cooperatively breeding stripe-backed wrens ( Campylorhynchus nuchalis ) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 92 publications
5
54
1
Order By: Relevance
“…Unlike dispersing males who frequently occupy neighbouring territories, observed female PBUs never dispersed to neighbouring territories. Our results differ from findings in other studies where females are reported to move to neighbouring groups as a staging post (Cockburn et al 2008;Eikenaar et al 2008) or to acquire breeding status in neighbouring territories (Curry and Grant 1990;Yáber and Rabenold 2002). While dispersal is presumably underestimated beyond the 30-ha plot because most territories fall within two territories of a plot edge, we did search outside the core area and we recorded all observed off-plot dispersal events.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike dispersing males who frequently occupy neighbouring territories, observed female PBUs never dispersed to neighbouring territories. Our results differ from findings in other studies where females are reported to move to neighbouring groups as a staging post (Cockburn et al 2008;Eikenaar et al 2008) or to acquire breeding status in neighbouring territories (Curry and Grant 1990;Yáber and Rabenold 2002). While dispersal is presumably underestimated beyond the 30-ha plot because most territories fall within two territories of a plot edge, we did search outside the core area and we recorded all observed off-plot dispersal events.…”
Section: Discussioncontrasting
confidence: 99%
“…We calculated home ranges for two antshrikes that returned at 0.58 and 0.30 ha (mean ¼ 0.44 ha, radius if circular ¼ 37 m) and for four wrens at 0.33, 0.31, 0.36, and 1.20 ha (mean ¼ 0.55, radius if circular ¼ 42 m) (Gillies and St. Clair 2010). These are similar to published results for congeners of both species, where home range radius was ;60 m for a congener to the antshrike in Brazil (T. caerulescens; Duca et al 2006) and ;75 m for a congener to the wren in Venezuela (Campylorhynchus nuchalis; Yaber and Rabenold 2002). Riparian corridors were typically 50-150 m wide.…”
Section: Translocations and Trackingsupporting
confidence: 86%
“…Although inbreeding or kin competition might often be avoided by short moves, greater distances are normally required to escape crowding conditions or to colonize vacant territories. Furthermore, dispersal distances, just like dispersal rates, may differ among sexes (Blundell et al 2002;Yaber and Rabenold 2002). Although short-distance dispersal is expected to display sex biases if kin avoidance plays an important role at a local scale, longdistance dispersal should not if colonization processes constitute the prevailing ultimate cause at this scale.…”
mentioning
confidence: 99%